Reliability of high-performance monolayer MoS2 transistors on scaled high-κ HfO2 - Hao-Yu Lan; Shao-Heng Yang; Karim-Alexandros Kantre; Daire Cott; Rahul Tripathi; Joerg Appenzeller; Zhihong Chen (npj 2D Materials and Applications)
Abstract The successful integration of ultrathin high-κ insulators is essential for the advancement of ultra-scaled field-effect transistors (FETs) based on two-dimensional (2D) semiconductors in future technology nodes. However, defects within the high-κ stack or at the interfaces can significantly degrade the performance of these “interface-only” devices, raising questions regarding their long-term reliability. Here, we study the reliability of monolayer MoS2 FETs on ultra-thin high-κ HfO2. Interestingly, we observe a two-stage threshold voltage shift (ΔV TH) under positive bias temperature stress (PBTS) and hot carrier degradation (HCD). This two-stage ΔV TH is absent in devices fabricated on exfoliated hBN, suggesting that the donor state generation (negative ΔV TH) is induced by atomic-layer-deposition (ALD) processes in HfO2-based devices. Elastic Recoil Detection Analysis (ERDA) indicates that hydrogen, likely from the ALD precursor, is a probable cause, highlighting the need for ALD process refinement to improve 2D FET stability for CMOS compatibility.